Adopting Neuroscience: Parenting and Affective Indeterminacy. (September 2017) - Mackenzie, Adrian; Roberts, Celia
What happens when neuroscientific knowledges move from laboratories and clinics into therapeutic settings concerned with the care of children? 'Brain-based parenting' is a set of discourses and practices emerging at the confluence of attachment theory, neuroscience, psychotherapy and social work. The neuroscientific knowledges involved understand affective states such as fear, anger and intimacy as dynamic patterns of coordination between brain localities, as well as flows of biochemical signals via hormones such as cortisol. Drawing on our own attempts to adopt brain-based parenting, and engaging with various strands and critiques of new materialism and affect theory, we explore the ways in which the social sciences and humanities might fruitfully engage with neuroscientific concepts and affects. How does science-affected indeterminacy, with all its promises of ontological and experiential agency, help us to observe, wait, bind or hold together volatile mixtures of habit, speech and action?